A Rare Case of Inguinal Hernia with Complete Bladder Herniation - Ayaaz Habib (Case Reports in Surgery)
Involvement of the bladder in inguinal hernias is rare and occurs in less than 5% of the cases. The diagnosis and management of this condition may present a challenge to the surgeon. We present a case of an elderly gentleman who presented with a large left-sided inguinoscrotal hernia causing an obstructive uropathy which was surgically repaired. The patient made a quick postoperative recovery with complete resolution of renal function.